O динамических уравнениях системы линейно связанных нелинейных осцилляторов - Бак, С.Н.; Панков, А.А. (Український математичний журнал, 2006)
Доведено теорему про гладкість узагальнених розв'язків диференціальних рівнянь з операторними коефіцієнтами. We consider a system of differential equations that describes the dynamics of an infinite chain of linearly coupled nonlinear oscillators. Some results concerning the existence and uniqueness of global solutions of the Cauchy problem are obtained.